2004
DOI: 10.1128/jb.186.10.3160-3172.2004
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Expression of the Polynucleotide Phosphorylase Gene ( pnp ) of Streptomyces : Processing of pnp Transcripts in Streptomyces antibioticus

Abstract: We have examined the expression of pnp encoding the 3-5-exoribonuclease, polynucleotide phosphorylase, in Streptomyces antibioticus. We show that the rpsO-pnp operon is transcribed from at least two promoters, the first producing a readthrough transcript that includes both pnp and the gene for ribosomal protein S15 (rpsO) and a second, Ppnp, located in the rpsO-pnp intergenic region. Unlike the situation in Escherichia coli, where observation of the readthrough transcript requires mutants lacking RNase III, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…To our knowledge, no such site has been demonstrated in E. coli. Although the start point for the pnp transcript has not been determined in S. coelicolor, studies from Streptomyces antibioticus suggest that the pnp transcript may not be cleaved by RNase III upstream of the coding region (2). If this is the case in S. coelicolor, the internal cleavage site explains the observation that the level of the pnp transcript, like that of the readthrough transcript, increases in the absence of RNase III (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…To our knowledge, no such site has been demonstrated in E. coli. Although the start point for the pnp transcript has not been determined in S. coelicolor, studies from Streptomyces antibioticus suggest that the pnp transcript may not be cleaved by RNase III upstream of the coding region (2). If this is the case in S. coelicolor, the internal cleavage site explains the observation that the level of the pnp transcript, like that of the readthrough transcript, increases in the absence of RNase III (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…In Streptomyces coelicolor and Streptomyces antibioticus, the phosphorolytic activity of PNPase is modulated by nucleoside diphosphates (11) and both phosphorolysis and polymerization are modulated by the alarmone, (p)ppGpp (13). As is the case in E. coli, the PNPase gene, pnp, is a part of an operon that includes the rpsO gene, which encodes ribosomal protein S15 (2). In E. coli, there is an intergenic hairpin, situated between rpsO and pnp, that is a site for processing by the double-strand-specific endonuclease, RNase III (17,29,30).…”
mentioning
confidence: 99%
“…RNA-Seq analysis of these preparations indicated that mRNA reads represented 64% of the total for M145 and and JSE1880 (rnc-null mutant). RT-PCR was performed as described previously (8,16), and products were analyzed after 20 PCR cycles to ensure linearity between band intensity and the number of cycles. Lane 1, size standards (the arrow indicates the 500-bp standard); lane 2, mRNA from M145 as the template for reverse transcription; lane 3, M145 BARD RNA; lane 4, M145 mock BARD RNA; lanes 5 and 8, JSE1880 mRNA; lanes 6 and 9, JSE1880 BARD RNA; lanes 7 and 10, JSE1880, mock BARD RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Reverse transcription-PCRs (RT-PCRs) were performed using random primers for reverse transcription and gene-specific primers for PCR as described previously (8,16). The results shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This 333 base fragment was produced by RNase III cleavage of a transcript obtained from a cloned DNA fragment representing the rpsO-pnp intergenic region (Bralley & Jones, 2004). The transcript was synthesized using T7 RNA polymerase and a-[ 32 P]CTP, and the 39-end of the RNase III digestion product represents the primary RNase III processing site in the rpsO-pnp intergenic region.…”
Section: Methodsmentioning
confidence: 99%